The Functional Significance of Synaptotagmin Diversity in Neuroendocrine Secretion - Moghadam, Paanteha K.; Jackson, Meyer B. (Frontiers in Endocrinology, 2013)
Synaptotagmins (syts) are abundant, evolutionarily-conserved integral membrane proteins that play essential roles in regulated exocytosis in nervous and endocrine systems. There are at least 17 syt isoforms in mammals, all with tandem C-terminal C2 domains with highly variable capacities for Ca2+ binding. Many syts play roles in neurotransmitter release or hormone secretion or both, and a growing body of work supports a role for some syts as Ca2+ sensors of exocytosis. Work in many types of endocrine cells has documented the presence of a number of syt isoforms on dense-core vesicles containing various hormones. Syts can influence the kinetics of exocytotic fusion pores and the choice of release mode between kiss-and-run and full-fusion. Vesicles harboring different syt isoforms can preferentially undergo distinct modes of exocytosis with different forms of stimulation. The diverse properties of syt isoforms enable these proteins to shape Ca2+ sensing in endocrine cells, thus contributing to the regulation of hormone release and the organization of complex endocrine functions.